A Literary Review on Allergic Dermatitis and its Treatment in Unani Medicine - Nusra, H.M.F.; Farzana, M.U.Z.N. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Dermatitis is a specific pattern of inflammatory changes of the skin. According to various criteria, eczema is divided in many ways. Allergic dermatitis is one of the types of eczema, which is a delayed hypersensitivity reaction of the skin in a sensitized individual. In the Unani Medicine, eczema is called Nar-e-farsi, and it is the result of raqeeq khilt (safra). The main causative factor is contact with the allergen, and according to Unani Medicine increases the production of Ghaire tabaee safra, joining with Ghair e tabaee Sawda, dam, and Balgham. The main objective of this review is to assess the effectiveness of Unani medicines on the treatment of Allergic Dermatitis. The Arabic and Persian manuscripts, like Al Qanun fī-al-Ṭibb, Kitab al Hawi fi-al-Tibb, Kitab Kamil aṣ-Ṣina ʿa aṭ-Ṭibbiyya, and Kitab al-Kulliyat were referred for the causes and management of Nar-e-farsi. Furthermore, the English-language literature on various scientific websites such as Google Scholar, PubMed, Cochrane, and Science Direct was browsed for contemporary approaches to manage Allergic dermatitis in complementary and alternative medicine. Terms such as allergic dermatitis, contact dermatitis, rash, eczema, herbs, complementary and alternative treatment for allergic dermatitis, and anti-allergic herbs were searched. In the inclusion criteria, the aforementioned terms and full-length freely accessible articles were included. Abstracts and articles other than English language were excluded. Unani drugs have immense potential in treating chronic and some acute disorders, and Unani system of medicine has several single and compound drugs to treat allergic dermatitis with proper advice successfully. It is potent, safe, affordable and gives a complete cure in most of the cases.
Keywords: Nar- e-farsi; Eczema; Allergic dermatitis; Unani treatment